Progesterone Therapy for the Prevention of Preterm Labor in Women with Single Risk-factor: A Systematic Review and Meta-analysis - Ara, Kefayat Chaman; Bahrami, Mohammad Amin; Bahrami, Elham; Bahrami, Sima; Bahrami, Mohammad Nabi; Moosazadeh, Mahmood; Barati, Omid (BALI MEDICAL JOURNAL; Vol 5 No 1 (2016), 2016)
Background: Preterm labor is a common complication of pregnancy which has become a main health concern around the world due to its negative consequences. Objective: To investigate the efficacy of progesterone therapy in the prevention of preterm labor in women with single risk factor. Search strategy: A PubMed, Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, Science Direct, Scopus, OVID, EMBASE, SID, Magiran and Google Scholar search (date last searched April 2016) without any time, language and location restriction was done. Inclusion criteria: All randomized clinical trials of singleton pregnancies with single risk factor (prior preterm labor without short cervical length or short cervical length without prior preterm labor) which were randomized to progesterone and control groups were included in our meta-analysis. Primary outcome: Our primary outcome was gestational age at delivery. Results: 13 studies (1259 subjects and 2653 control women) were included in the meta-analysis. Using random effect model showed that mean gestational age at delivery of progesterone group is 0.74 (0.41-1.06) month longer than that of control group with CI=95% which is significant statically. Conclusions: Progesterone therapy is an effective intervention for the prevention of preterm labor in women with single risk factor.
Keywords: Preterm birth, Preterm labor, Previous preterm labor, Progesterone, Short cervical length.